(untitled) (PANGEEA, 2025)
Zlatna town in the context of urban regeneration. The complex problems regarding the deprived Area of Zlatna were identified and analyzed both during the functioning period of SC Ampelum SA and after the activity of the company ended (2004). The ecological reconstruction of this area is a long process and requires a series of projects regarding the re-habilitation of this area, administrative measures, solid financial resources and the ecological education of its inhabitants. This article has the role to give information about aspects such as: concept of urban revitalization (a new concept used in the integrated territorial planning activities), the opportunities the deprived Area of Zlatna offers to the investors, the minimal requirements necessary for an environmental conversion process and the main projects finalized or those which are in progress in the deprived Area of Zlatna.